Analisis Ketimpangan, Pola Pertumbuhan Ekonomi dan Sektor Unggulan di Kawasan Kedungsepur Provinsi Jawa Tengah - Dzikri Ainun Faza; Dwi Susilowati; Zainal Arifin (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2023)
One of the efforts regarding equitable development to accelerate regional economic development is through infrastructure development in priority areas and can also help restore the community's economy due to Covid-19 in the Kedungsepur Area, Central Java Province. Based on Presidential Regulation No. 79 of 2019 it is stated that increasing investment and economic growth in the region has an impact. To know the level of income inequality, economic growth patterns, and leading sectors for a decade. By using data obtained from one of the institutions, namely the Central Bureau of Statistics, is processed using the analysis techniques of the Williamson Index, Klassen Typology, LQ/SLQ-DLQ. The results of the analysis showed that the lowest level of inequality reached 0.179 in 2013 while for the growth pattern there was 1 fast growing and growing, 1 developing fast, 4 underdeveloped and leading sub-sectors that still had the potential to have 5 sectors with classification for the leading economic sector from 6 districts/cities there were 25 featured categories 32 mainstays, 19 prospective and 26 lagging